2019
DOI: 10.1002/mds.27876
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism Associated with Gabapentinoid Drugs: A Pharmacoepidemiologic Study

Abstract: Background Use of gabapentinoids is increasing. Following recent case reports, we investigated a putative risk of parkinsonism with pregabalin or gabapentin. Methods A disproportionality analysis of 5,653,547 individual case safety reports in the World Health Organization individual case safety report database, VigiBase, compared all patients with parkinsonism who were receiving gabapentinoids with other patients. Results are shown as reporting odds ratios and the information component, an indicator of disprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…For the years 1999 and 2019, a total of 46 reports containing 305 cases who developed MDs after the use of PGB from 17 different countries were reported [ Table 1 ]. [ 2 3 10 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 ] The origin was North American in 196, European in 68, Asian in 40, and South American in 1. The MDs associated with PGB found were as follows: 184 patients with ataxia, 61 with tremors, 39 with MCL, 8 with parkinsonism, 1 with restless legs syndrome, 1 with dystonia, 1 with dyskinesia, and 1 with akathisia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the years 1999 and 2019, a total of 46 reports containing 305 cases who developed MDs after the use of PGB from 17 different countries were reported [ Table 1 ]. [ 2 3 10 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 ] The origin was North American in 196, European in 68, Asian in 40, and South American in 1. The MDs associated with PGB found were as follows: 184 patients with ataxia, 61 with tremors, 39 with MCL, 8 with parkinsonism, 1 with restless legs syndrome, 1 with dystonia, 1 with dyskinesia, and 1 with akathisia.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles did not report the number of patients, but they observed MCL[ 39 54 ] and parkinsonism. [ 49 ]…”
Section: Resultsmentioning
confidence: 99%
“…We have read "Parkinsonism associated with gabapentinoid drugs: a pharmacoepidemiologic study" by Pacheco-Paez and colleagues with great interest. 1 As the use of gabapentinoid drugs increases, any information on their possible long-term side effects is warranted. Based on the VigiBase database, the researchers concluded that both gabapentin (GBP) and pregabalin (PRG) have 2.16 to 2.43 times higher reporting odds ratios (RORs) for developing parkinsonism than nonusers, indicating possible adverse reactions.…”
mentioning
confidence: 99%
“…Dávid Pintér, MD, 1 József Janszky, MD, DSc, 2,3 and Norbert Kovács, MD, DSc We read with interest the comments by Pinter and colleagues about our article in which we suggested an association between exposure to gabapentinoids (gabapentin, pregabalin) and the occurrence of parkinsonism. 1 The authors discussed several points.…”
mentioning
confidence: 99%
See 1 more Smart Citation